PENGARUH VIRTUAL LEARNING BERBASIS DEEP LEARNING TERHADAP MOTIVASI BELAJAR EKONOMI SISWA SMA NEGERI 8 TERNATE - Nazwa Nabila; Febiyanti Umaternate; Ode Zulaeha (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
The increasingly dynamic development of the global economy demands improvements in human resource quality through education, including in the field of economics. However, students' low understanding of basic economic concepts remains a major issue across various educational institutions. This study aims to analyze the effectiveness of implementing the Problem-Based Learning (PBL) model in enhancing high school students' understanding of economic concepts. A quasi-experimental method with a pretest-posttest control group design was employed. The research sample consisted of two 11th-grade social science classes (XI IPS) at a public high school in Ternate, selected using purposive sampling. Data were collected through a concept comprehension test and analyzed using a t-test. The results indicate a significant difference in the average post-test scores between students who were taught using the PBL model and those who received conventional instruction. The PBL model proved more effective in improving students’ conceptual understanding of economics by encouraging critical, collaborative, and contextual thinking in solving real-world economic problems. In conclusion, the implementation of the Problem-Based Learning model has a positive impact on students’ comprehension of economic concepts. This study recommends the adoption of PBL as an alternative instructional strategy in economics education, particularly at the secondary school level.